'Mess, stress and trauma': students' experiences of formal contract cheating processes. Issue 4 (19th May 2021) - Pitt, Penelope; Dullaghan, Kevin; Sutherland-Smith, Wendy
Abstract: Contract cheating is concerning educational institutions across the globe. Current knowledge of student perspectives on contract cheating is primarily informed by student surveys. Little is known about the student experience of being suspected of contract cheating and going through a formal university process. This study reports the findings of a qualitative study at an Australian university with student participants who had faced contract cheating allegations, using semi-structured, in-depth interviews. Five key themes emerged: 1) the most challenging experience of the student's life; 2) not telling their family about the allegation and managing any financial impact themselves; 3) stress and hypervigilance around future assignment submission; 4) rumours and reputational damage including changed relationships with academics and peers; and, 5) staying on track and guiding other students to practice academic integrity. Participants perceived the formal university process as a legal one, which contributed to it being a stressful and challenging experience. This was regardless of whether they had contract cheated or not. Recommendations for academic and support staff centre around ensuring formal university contract cheating processes are primarily a learning experience, from which students can emerge and progress to complete their studies.